2015
DOI: 10.1111/asj.12368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monensin withdrawal on rumen fermentation, methanogenesis and microbial populations in cattle

Abstract: This study was designed to obtain information on the residual influence of dietary monensin on ruminant fermentation, methanogenesis and bacterial population. Three ruminally cannulated crossbreed heifers (14 months old, 363 ± 11 kg) were fed Italian ryegrass straw and concentrate supplemented with monensin for 21 days before sampling. Rumen fluid samples were collected for analysis of short chain fatty acid (SCFA) profiles, monensin concentration, methanogens and rumen bacterial density. Post-feeding rumen fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
(56 reference statements)
1
7
0
1
Order By: Relevance
“…There have been a number of experiments with monensin as a rumen modifier in various production systems, where CH 4 production was studied as a main objective either from a mitigation or from an energy loss perspective. [33][34][35][36] Although some studies reported a long-term mitigating effect of monensin on CH 4 production, overall the effect of the ionophore on methane production appears to be inconsistent, transient and short-lived indicating that microbial adaptation occurs.…”
Section: Bacteriocins and Ionophoresmentioning
confidence: 99%
“…There have been a number of experiments with monensin as a rumen modifier in various production systems, where CH 4 production was studied as a main objective either from a mitigation or from an energy loss perspective. [33][34][35][36] Although some studies reported a long-term mitigating effect of monensin on CH 4 production, overall the effect of the ionophore on methane production appears to be inconsistent, transient and short-lived indicating that microbial adaptation occurs.…”
Section: Bacteriocins and Ionophoresmentioning
confidence: 99%
“…After 24 h of incubation, all bottles were cooled on ice to stop fermentation and sampled to determine headspace gas composition, dry matter degradability, short-chain fatty acids (SCFAs), methane generation, and the gene (mcrA). Analyses were conducted as described previously (Denman et al, 2007;Abrar et al, 2015). Real-time PCR for the quantification of mcrA copy number was performed on a StepOnePlus Real-Time PCR Systems (Applied Biosystems, Foster City, CA USA).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…MSS was supplemented at 0, 40, 80 mg/kg (dry matter of substrate); DF was added into serum bottles in vitro, and the final treatment concentrations were 0, 7, and 14 mmol/L (Table 1). The concentrations of MSS and DF were slightly adjusted according to previous studies [10,12,14,17]. Incubation substrate (450 mg) was dispensed into a 100 mL serum bottle with an appropriate amount of MSS and/or DF, and then 45 mL artificial rumen inoculum was transferred into each bottle under anaerobic conditions.…”
Section: In Vitro Rumen Incubationmentioning
confidence: 99%
“…There are two main mechanisms to effectively abate CH 4 formation this way [8]: the first is to maintain a low H 2 pressure by inhibiting H 2 liberating reactions. Monensin is an ionophore that can effectively inhibit hydrogen-producing microorganisms (Gram-positive bacteria and protozoa), resulting in more propionate, which means less acetate, formate, butyrate and hydrogen are produced in the rumen [9,10]. Monensin has been shown to decrease the methane emissions of rumen [11,12].…”
Section: Introductionmentioning
confidence: 99%